"There's no money in community dissemination": A mixed methods analysis of researcher dissemination-as-usual. Issue 1 (1st August 2022) - Uphold, Heatherlun S.; Drahota, Amy; Bustos, Tatiana E.; Crawford, Mary Katherine; Buchalski, Zachary
Abstract: Background: The field of dissemination and implementation science has the potential to narrow the translational research-to-practice gap and improve the use of evidence-based practices (EBPs) within community-based settings. Yet, foundational research related to dissemination efforts, such as understanding researcher attitudes, practices, and the determinants to sharing research findings, is lacking within extant literature. Methods: A sequential explanatory (QUAN $$ → $$ qual) mixed methods design was used to examine 85 academic researchers' perspectives and self-reported dissemination methods used to share research outcomes with community stakeholders to better understand researcher's usual dissemination practices (referred to as dissemination-as-usual ). Quantitative surveys collected researcher demographic data, attitudes toward dissemination efforts, and dissemination strategy use. Results: Multiple linear regression examined predictors of the quantity of dissemination strategies utilized by researchers, finding that years since earning their degree, time spent disseminating, and the number of reasons for engaging in dissemination efforts predicted greater numbers of dissemination strategies utilized by researchers. Individual, semi-structured interviews with a subset of researchers ( n = 18) expanded upon quantitative findings, identifying barriers and facilitators to their dissemination efforts. Data strands were integrated using a joint display, and the Dissemination of Research model guided data interpretation. More established researchers experienced fewer barriers and more facilitators to support their use of a variety of dissemination strategies to share findings with community stakeholders. However, researchers reported needing specific training, institutional support, and/or dedicated time to plan and enact dissemination strategies. Conclusion: The necessary first step in research translation is the dissemination of research evidence, and understanding dissemination-as-usual can identify areas of need to advance translational science.